1995
DOI: 10.1093/ajcp/103.4.438
|View full text |Cite
|
Sign up to set email alerts
|

The Cytopathology of Proliferative Breast Disease:Comparison With Features of Ductal Carcinoma In Situ

Abstract: Epithelial hyperplasia, a component of proliferative breast disease (PBD), is a known risk factor for the development of breast carcinoma. To determine if criteria established for tissue biopsy could be used to more precisely define cytologic criteria for diagnosis of PBD, 37 breast fine-needle aspirates with biopsy diagnoses of PBD were studied. In cases with adequate cellularity, the following findings were consistently observed: (1) three-dimensional cell clusters with outlying myoepithelial cells, swirling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The scoring systems proposed by Page et al [11] and Dawson AE et al [6] have consistently found that architectural features like three-dimensional epithelial clusters, swirling or streaming of intraluminal cells and peripheral slit-like irregular lumen helped to differentiate PBD without atypia from ductal carcinoma insitu (DCIS), the findings which were supported by Sneige and Staerkel. [12] Most studies for scoring of breast lesions use traditional cytologic features that include cellularity, nuclear pleomorphism, overlap and loss of polarity.…”
Section: Introductionmentioning
confidence: 82%
“…The scoring systems proposed by Page et al [11] and Dawson AE et al [6] have consistently found that architectural features like three-dimensional epithelial clusters, swirling or streaming of intraluminal cells and peripheral slit-like irregular lumen helped to differentiate PBD without atypia from ductal carcinoma insitu (DCIS), the findings which were supported by Sneige and Staerkel. [12] Most studies for scoring of breast lesions use traditional cytologic features that include cellularity, nuclear pleomorphism, overlap and loss of polarity.…”
Section: Introductionmentioning
confidence: 82%
“…This cytologic pattern, in the context of either unsuspected or abnormal clinical/mammographic findings, requires follow-up biopsy to rule out carcinoma since the cytologic distinction between atypical ductal hyperplasia, in situ and even invasive ductal carcinoma is often not possible, although it has been attempted by some authors. 1,3,8,17 Atypical Fibroadenoma-Like Tumor (Cannot Rule Out Phyllodes Tumor)…”
Section: Proliferative Fibrocystic Changes With Atypia (Atypical Ductmentioning
confidence: 99%
“…Many authors have used various means to come to a conclusive method of diagnosis by FNAC of breast lesions [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%